Interestmeasurement and system construction of personal information protectionLI Meiyan - 李美燕 (Dianxin kexue)
Massive data always records the trajectory of people’s production and life.Through analysis andmining,it can provide personalized and accurate services for netizens.But the greateRthe intensity of data utilization,the greateRthe risk of personal information protection,and the imbalance ismore serious and common.Exploring the way of protecting personal information in China requiresmeeting the practi cal needs of digital China.Firstly,taking United States,European Union,and China as examples,the legislative path andmode of personal information protection were introduced.Then,the characteristics of personal information protection in China were analyzed.Finally,the balance of interests and system of personal information protection was considered.